UNIVERSITY YOUTH TRENDS TOWARDS CYBERBULLYING – A field study by application on Twitter users – - Alshahrani, Abrar Mohammed Al -Habshan (Journal of Humanities & Social Sciences, 2021)
The Studies aimed to know the perspectives of Saudi University Students on the phenomenon of Cyberbullying. We used an available sample of (300) young men and women (Twitter) users from various universities in KSA, whose ages are between (17-35) years using the Survey. The Studies used Descriptive Analytical and Field Survey Methods to evaluate the perspectives of university students on the phenomenon of Cyberbullying in Twitter. The most important results of the Studies are; the results of the Studies confirmed that Most samples at 90.7% were getting bullied, which confirms the prevalence of bullying and raises concerns. Most samples agreed that the large numbers of active fake accounts on Twitter at 88.3% is the most important reason for Cyberbullying prevalence. The results of the studies showed that the most prevalent type of Cyberbullying was (direct bullying) at 79.7%. Most samples at 76% agreed that (bullying is a dangerous phenomenon on Twitter that requires taking firm procedures to stop it). Moreover, the Studies recommended the following; installing an application of (Kollona Amn) extensively by cooperating with telecommunications companies in KSA to provide citizens with all updates regarding security measures and deterrent controls. The application spreads awareness of rights and security measures between citizens to confront all electronic crimes including bullying crimes. Issuing more legislations and deterrent laws regarding cybercrimes and imposing penalties on bullies, in order to strengthen the importance of Law in our community service to preserve the safety of the individual and society. Using Cybersecurity to teach and show the youth and the younger generation the limits of liberty on Social Media by publishing documentaries, educational programs and advertisements on the most prominent used media in KSA.